Optimization of peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) method for the detection of bacteria: the effect of pH, dextran sulfate and probe concentration - Rocha, Rui (2014)
Fluorescence in situ hybridization (FISH) appeared in the 1980’s and is nowadays widely used in the field of microbiology. FISH is affected by a wide variety of abiotic and biotic variables and their interplay. This is translated into a wide variability of FISH procedures that can be found in the literature. The aim of this work is to study the effects of pH, probe and dextran sulphate concentration in the FISH protocol. For this, response surface methodology (RSM) was used to optimize FISH protocol for gram-negative (E. coli and P. fluorescens) and gram-positive bacteria (L. innocua, S. epidermidis and B. cereus), for these 3 parameters. The obtained results show a clear distinction between the two groups: higher pH (>9) combined with lower dextran sulphate concentration (<2.5% [w/v]); for Gram-negative bacteria and pH from 6.5 to 9 together with higher dextran sulphate concentrations (>7% [w/v]), for Gram-positive bacteria. The optimal probe concentration was the same for both groups (300 nM). These results seem to result from an interplay of pH and dextran sulphate ability to influence the probe concentration and migration inside the bacteria.